Second record of Erythraeus (Zaracarus) coleopterus (Acari: Erythraeidae) from Iran with new morphological data - Javad Noei; Mostafa Maroufpoor; Fardin Faizi; Hadi Ostovan (Persian Journal of Acarology)
Erythraeus (Zaracarus) coleopterus Mortazavi, Hajiqanbar & Saboori, 2012 (Acari: Parasitengona: Erythraeidae) was described based on a single specimen from Kerman province, southeastern Iran, associated with a scarabaeid beetle, Cyphonoxia sp. (Coleoptera: Scarabaeidae). This species reports for the second time from stored grain (off host) in Saqqez and Baneh cities, Kurdistan province, western Iran and presents new morphological data. Finding some specimens help us to augment and correct the original description of E. (Z.) coleopterus. A key to world larval species group of Erythraeus (Zaracarus) is presented which is modified and corrected from Mahmoudi et al. (2014).